أثر استخدام استراتيجية التساؤل الذاتي فى تنمية مستويات الفهم القرائي للنصوص الأدبية - عجيل، رجاء عبد السلام محمد (Kulliyah of Education, International Islamic University Malaysia, 2018)
Despite the importance of reading comprehension with regard to literary texts, there exists an unmistakable inadequacy of traditional teaching methods to develop reading comprehension skills. As a natural result this insfficiency this research came to examine the effect of teaching using self-questioning strategy on developing the reading comprehension skills of first grade secondary school students. The research aimed to identify the impact of teaching using self-questioning strategy on developing the levels of comprehension skills (direct, deductive, critical, segnification, creative) of literary texts for first year secondary school students in Misrata City. In order to achieve -the research objectives, the researcher used the descriptive and the quasi-experimental methodological approaches. The research sample was comprised of (83) students: two experimental groups of (41) students and two control groups of (42) students, were selected from the population of (5073) first year secondary school students in Misrata city, Libya. The research used the following tools: a list of reading comprehension skills, a reading comprehension test, and bookguides for both teachers and students prepared according to the self questioning strategy. Once the psychometric stabilities of the research tools were examined , they were applied on the research sample for eleven weeks. The results showed that the reading comprehension skills were reached fourteen skills categorized into five levels. There were significant differences at (0.05) in all the reading comprehension skills (the direct comprehension level, deductive comprehension level , critical comprehension level, gastronomic comprehension level, and the creative comprehension level), in favor of the two experimental groups which used the self questioning strategy in teaching . There were no significant differences in the means of the students- scores on the post reading comprehension test of literary texts using self questioning strategy in developing the direct comprehension level , deductive comprehension level, segnification comprehension level ,and creative comprehension level due to the gender variable. For the level of critical comprehension, the difference was significant in favor of the female group.